STATISTICAL STUDY ON THE ANTHROPOMETRIC PROFILE OF THE GYMNASIUM CYCLE STUDENTS FROM "IORGU VÂRNAV LITEANU" HIGHSCHOOL, LITENI - Mihai Ciubotaru; Bogdan Grosu (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
One of the most important concerns of man is to establish the physical dimensions of the human body. Anthropometric evaluation is a method of quantifying growth and physical development based on body measurement. In conducting anthropometric measurements, it is recommended to use the same instruments for all students, such as telemeter, metric tape, mobility scales, etc. This paper aims at presenting somatic evaluation methods at gymnasium level and anthropometric exam on harmonious growth and development that is an important activity in physical education and sports, because through these measurements we can check whether pupils fall within normal limits below or exceeds the normal level by age and gender.